Positive lithium supplement agent and preparation method thereof, positive pole piece, battery and electric equipment
By forming a dense and uniform carbon cladding layer on the surface of the lithium supplement core of the positive electrode lithium supplement agent, the problem of insufficient conductivity and environmental tolerance is solved, and the energy density and cycle life of the lithium-ion battery are improved.
Patent Information
- Application Number
- CN202411756487.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The existing positive electrode lithium supplement agents have poor conductivity and insufficient environmental tolerance, resulting in poor energy density and cycle life of lithium-ion batteries.
By forming a dense, uniform and excellent conductivity carbon cladding layer on the surface of the lithium supplement core, the peak intensity relationship between G peak, D peak and 1 peak in the Raman spectrogram is used to control the degree of graphitization and disorder of the carbon cladding layer, thereby improving conductivity and improving environmental tolerance.
It significantly improves the conductivity and environmental tolerance of the positive electrode lithium supplement agent, extends the cycle life of the battery, and improves the efficiency of the first circle of the Coulomb.
Smart Images

Figure CN119786602A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a positive electrode lithium supplement and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art
[0002] With the rapid development of the new energy field and the improvement of people's living standards, the requirements for the battery life and service life of digital devices and electric vehicles are getting higher and higher. Therefore, how to improve the energy density and cycle life of lithium-ion batteries is a research hotspot in the battery field. The consumption of lithium ions is an important reason for the attenuation of battery capacity, especially during the first charge and discharge of the battery, the electrolyte forms a SEI film on the surface of the negative electrode, which consumes a large amount of active lithium, resulting in irreversible capacity loss of the battery.
[0003] Lithium replenishment is an important means of adding extra active lithium to lithium-ion batteries to offset the energy density decay caused by active lithium consumption. Conventional lithium replenishment methods include negative electrode lithium replenishment and positive electrode lithium replenishment. Among them, negative electrode lithium replenishment requires the use of n-butyl lithium or lithium metal, etc., which is difficult and dangerous to replenish lithium and difficult to apply industrially. Positive electrode lithium replenishment is to add compounds that are easy to delithium under high pressure to the positive electrode. Its use is relatively safe and convenient for industrial application.
[0004] Currently commonly used positive electrode lithium supplements include Li 5 FeO 4 , Li 2 NiO 2 , Li 6 CoO 4 , Li 2 O 2 etc., which generally have the problem of poor conductivity. 5 FeO 4 For example, its conductivity is very low, only 10 -9 S / cm level, which is almost an insulating compound. In the prior art, the conductivity of the material is usually improved by metal doping, carbon layer coating and other means. However, the above means have limited improvement on the intrinsic conductivity of the material, and it is still difficult for the material to fully exert its lithium replenishment characteristics. In addition, the density of the coating layer is poor, resulting in poor environmental tolerance of the positive electrode lithium replenisher, easy absorption of moisture, and high residual alkali content. Summary of the invention
[0005] The present invention provides a positive electrode lithium replenisher, a positive electrode plate, a battery and an electrical device. The inner core surface of the positive electrode lithium replenisher of the present invention comprises a dense and uniform carbon coating layer with excellent conductivity. The coating layer can better isolate the lithium replenisher inner core from the air, improve the environmental tolerance of the positive electrode lithium replenisher, reduce the residual alkali content on the surface, and greatly improve the conductivity of the positive electrode lithium replenisher, which is conducive to fully exerting the lithium replenishment capacity.
[0006] The first aspect of the present invention provides a positive electrode lithium supplement agent, comprising a lithium supplement core and a carbon coating layer coated on the surface of the lithium supplement core;
[0007] The Raman spectrum of the positive electrode lithium supplement has a shift interval of 1560-1580cm -1 The G peak and displacement range are 1350~1370cm -1 The D peak and displacement range are 655~675cm -1 1 peak;
[0008] Among them, the peak intensity IG of the G peak, the peak intensity ID of the D peak and the peak intensity I1 of the 1 peak satisfy: 0.85 < IG / ID <1.25, 9 < IG / I1 <50, 9 < ID / I1 <50.
[0009] The positive electrode lithium supplement agent as described above, wherein the positive electrode lithium supplement agent is obtained by sintering a mixture including a lithium supplement core, a carbon source and a coating additive;
[0010] The coating additive includes a compound that can be thermally decomposed to generate gaseous carbon-halogen free radicals and halogen free radicals, and the temperature of the thermal decomposition is not higher than the temperature of the sintering treatment.
[0011] The positive electrode lithium supplement as described above, wherein the molecular weight of the coating additive is less than 600.
[0012] The positive electrode lithium supplement as described above, wherein the coating additive includes one or more of hexachlorobenzene, hexabromobenzene, chlorobenzene, bromobenzene, dichlorobenzene, and dibromobenzene.
[0013] The positive electrode lithium supplement agent as described above, wherein the chemical composition of the lithium supplement core is Li a M b O c , wherein M includes one or more of Fe, Ni, Mn, Cu, Zn, Co, Cr, Zr, Sb, Ti, V, Mo, and Sn, 1<a≤8, 0<b≤1, and 0<c<7.
[0014] The positive electrode lithium supplement as described above, wherein the carbon source includes one or more of carbon black, graphene, carbon nanotubes, fullerenes, sucrose, glucose, asphalt, polydopamine, resorcinol, formaldehyde, starch, sucrose, sodium carboxymethyl cellulose, polyvinylidene fluoride, polyvinyl pyrrolidone, tannic acid, polyvinyl alcohol, polypyrrole, vitamin C, polyethylene glycol, anthracene or aniline.
[0015] The positive electrode lithium supplement agent as described above, wherein the mass ratio of the lithium supplement core, the carbon source and the coating additive is 1:x:y, 0 <x<10%,0<y<10%。
[0016] The positive electrode lithium supplement as described above, wherein the D50 particle size of the positive electrode lithium supplement is 10-30 μm.
[0017] The positive electrode lithium supplement agent as described above, wherein the thickness of the carbon coating layer of the positive electrode lithium supplement agent is 100-200 nm.
[0018] The positive electrode lithium supplement agent as described above, wherein the specific surface area of the positive electrode lithium supplement agent is 0.3-0.8 m 2 / g.
[0019] A second aspect of the present invention provides a method for preparing the positive electrode lithium supplement as described above, comprising the following steps:
[0020] The lithium supplement core, the carbon source and the coating additive are mixed to obtain a mixture; the mixture is sintered to obtain a positive electrode lithium supplement agent;
[0021] The coating additive includes a compound that can be thermally decomposed to generate gaseous carbon-halogen free radicals and halogen free radicals, and the temperature of the thermal decomposition is not higher than the temperature of the sintering treatment.
[0022] In the preparation method as described above, the sintering treatment is performed at a temperature of 80 to 1000° C. and for a time of 3 to 15 hours.
[0023] A third aspect of the present invention provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one side surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode lithium supplement as described above.
[0024] A fourth aspect of the present invention provides a battery, comprising the positive electrode plate as described above.
[0025] A fifth aspect of the present invention provides an electrical device comprising the battery as described above.
[0026] The implementation of the present invention has at least the following beneficial effects:
[0027] 1) The positive electrode lithium supplement agent of the present invention comprises a lithium supplement core and a carbon coating layer coated on the surface of the lithium supplement core. The Raman spectrum of the positive electrode lithium supplement agent has a shift interval of 1560-1580cm -1 The G peak and displacement range are 1350~1370cm -1 The D peak and displacement range are 655~675cm -11 peak; by limiting the peak intensity IG of the G peak, the peak intensity ID of the D peak and the peak intensity I1 of the 1 peak to satisfy: 0.85 < IG / ID <1.25, 9 < IG / I1 <50, 9 < ID / I1 <50, the surface of the lithium replenishing core is distributed with an appropriate amount of bulk carbon with a high degree of graphitization and edge carbon with a high degree of disorder, forming a dense, uniform and highly conductive carbon coating layer, which can better isolate the lithium replenishing core from the air, improve the environmental tolerance of the positive electrode lithium replenishing agent, reduce the surface residual alkali content, and at the same time greatly improve the conductivity of the positive electrode lithium replenishing agent, which is conducive to giving full play to the lithium replenishing capacity.
[0028] 2) The preparation method of the positive electrode lithium supplement agent provided by the present invention comprises the following steps: preparing the positive electrode lithium supplement agent by mixing a lithium supplement core, a carbon source and a coating additive and then sintering the mixture; wherein the coating additive comprises a compound that can thermally decompose to generate gaseous carbon-halogen free radicals and halogen free radicals, and the thermal decomposition temperature is not higher than the sintering temperature; during the sintering process, the coating additive can thermally decompose to generate gaseous carbon-halogen free radicals ( ) and halogen radicals ( ), highly active halogen radicals can combine with carbon source materials to generate more gaseous carbon-halogen free radicals, greatly increasing the concentration of gaseous carbon-halogen free radicals. At this time, the lithium-supplemented core is exposed to a high concentration of gaseous carbon-halogen free radical atmosphere, and the solid-gas two phases ensure sufficient contact between the two. After the gaseous carbon-halogen free radicals undergo dehalogenation reaction on the surface of the lithium-supplemented core, a dense and uniform carbon coating layer can be generated in situ.
[0029] 3) Since the positive electrode plate and battery provided by the present invention include the above-mentioned positive electrode lithium replenisher, they can replenish the active lithium loss of the battery during the initial charge and discharge process and the cycle process, so that the battery has a higher first-cycle coulomb efficiency and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 A schematic diagram of the structure of a traditional positive electrode lithium supplement;
[0031] Figure 2 This is a schematic structural diagram of a positive electrode lithium supplement according to an embodiment of the present invention;
[0032] Figure 3 This is a Raman spectrum of the positive electrode lithium supplement agent of Example 11;
[0033] Figure 4 This is a SEM image of the positive electrode lithium supplement agent of Example 1;
[0034] Figure 5 This is the SEM image of the positive electrode lithium supplement agent of Comparative Example 1.
[0035] Description of reference numerals:
[0036] 11-lithium-supplemented core; 22-carbon coating layer; 33-pores. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Traditional positive electrode lithium supplements, such as Li 5 FeO 4 , Li 2 NiO 2 , Li 6 CoO 4 , Li 2 O 2 The band gap is large, the conductivity is poor, and it is unstable to the environment. Therefore, conductive carbon materials are usually used to coat its surface. The coating layer can improve the conductivity of the lithium supplement agent and isolate the lithium supplement active material from the air to prevent it from reacting with moisture and carbon dioxide in the air. However, the traditional coating layer has poor density, which makes the protection of the internal lithium supplement active material limited. Figure 1 is a schematic diagram of the structure of a traditional positive electrode lithium supplement, such as Figure 1 As shown, the lithium supplement agent includes a lithium supplement core 11 and a carbon coating layer 22, wherein the carbon coating layer 22 further includes holes 33 penetrating the surface of the lithium supplement core. The presence of the holes 33 ensures that the lithium supplement core still has a certain contact area with the air, so that the isolation and protection effect of the carbon coating layer is limited. Finally, the residual alkali content on the surface of the positive electrode lithium supplement agent is still high, the electrical conductivity of the material is still low, and the lithium supplement capacity still needs to be improved.
[0039] Based on this, the present invention provides a positive electrode lithium supplement agent, Figure 2 FIG. 1 is a schematic diagram of the structure of a positive electrode lithium supplement according to an embodiment of the present invention. Figure 2 As shown, the positive electrode lithium supplement agent of the present invention comprises a lithium supplement core 11 and a carbon coating layer 22 coated on the surface of the lithium supplement core; wherein the Raman spectrum of the positive electrode lithium supplement agent has a displacement interval of 1560-1580cm -1 The G peak and displacement range are 1350~1370cm -1 The D peak and displacement range are 655~675cm -1 1 peak;
[0040] Among them, the peak intensity IG of the G peak, the peak intensity ID of the D peak and the peak intensity I1 of the 1 peak satisfy: 0.85 < IG / ID <1.25, 9 < IG / I1 <50, 9 < ID / I1 <50.
[0041] Among them, the G peak is the sp 2 Hybrid peaks are mostly bulk carbon peaks. Bulk carbon refers to the carbon atoms inside the carbon crystal, which are surrounded by saturated pairs. The more bulk carbon there is, the higher the graphitization degree of the carbon coating layer is, the larger the flakes are, the higher the degree of two-dimensional plane spreading is, and the higher the conductivity is. However, if the flakes are too large, it is not conducive to the densification of carbon materials on the surface of the lithium-supplemented core. The D peak is the edge carbon and sp 3 The peaks of hybrid carbon, among which edge carbon refers to the carbon at the edge of the carbon crystal, and there are unsaturated pairs around it. The higher the intensity of peak D, the higher the degree of disorder of the carbon material, indicating that the carbon material tends to be more point-like. The smaller the flakes, the more conducive to the densification of the carbon material on the surface of the lithium supplement core. However, if the degree of disorder is too high, it is not conducive to the carbon coating layer to exert good conductivity. Peak 1 is the bond vibration peak of the metal element and oxygen of the lithium supplement core material. Its peak intensity reflects the exposure degree of the lithium supplement core. The higher the peak intensity of peak 1, the incomplete coating of the carbon coating layer. If the peak intensity of peak 1 is too low, it means that there is too much carbon material in the outer layer, which leads to increased resistance to lithium ion deintercalation and affects the electrochemical properties of the material.
[0042] The present invention controls the peak intensity IG of the G peak, the peak intensity ID of the D peak and the peak intensity I1 of the I peak in the Raman spectrum of the positive electrode lithium supplement agent to satisfy: 0.85<IG / ID<1.25, 9<IG / I1<50, 9<ID / I1<50, so that the surface of the lithium supplement core is distributed with an appropriate amount of bulk carbon with a high degree of graphitization and edge carbon with a high degree of disorder, forming a dense, uniform and highly conductive carbon coating layer, which can better isolate the lithium supplement core from the air, improve the environmental tolerance of the positive electrode lithium supplement agent, reduce the surface residual alkali content, and greatly improve the conductivity of the positive electrode lithium supplement agent, which is conducive to giving full play to the lithium supplement capacity.
[0043] As a preferred embodiment, the positive electrode lithium supplement agent is obtained by sintering a mixture including a lithium supplement core, a carbon source and a coating additive, wherein the coating additive includes a compound that can thermally decompose to produce gaseous carbon-halogen free radicals and halogen free radicals, and the thermal decomposition temperature is not higher than the sintering treatment temperature.
[0044] During the sintering process, the coating additives can be thermally decomposed to produce gaseous carbon halide free radicals ( ) and halogen radicals ( ), highly active halogen radicals can combine with carbon source materials to generate more gaseous carbon-halogen free radicals, greatly increasing the concentration of gaseous carbon-halogen free radicals. At this time, the lithium supplement core is exposed to a high concentration of gaseous carbon-halogen free radical atmosphere, and the solid-gas two phases ensure full contact between the two. After the gaseous carbon-halogen free radicals undergo dehalogenation reaction on the surface of the lithium supplement core, a dense and uniform carbon coating layer can be generated in situ, which better isolates the lithium supplement core from the air, and prevents the lithium supplement core from reacting with components such as moisture and carbon dioxide in the air to deteriorate, thereby improving the environmental tolerance of the positive electrode lithium supplement agent, reducing the residual alkali content on the surface, and facilitating slurry coating. At the same time, the dense carbon coating layer greatly improves the conductivity of the positive electrode lithium supplement agent, which is conducive to the full utilization of the lithium supplement capacity.
[0045] The molecular weight of the coating additive added as above should not be too large, otherwise it is difficult to generate gaseous carbon-halogen free radicals and halogen free radicals after thermal decomposition. Based on the above considerations, the molecular weight of the coating additive is preferably <600, more preferably <300.
[0046] In a specific embodiment, the coating additive includes one or more of hexachlorobenzene, hexabromobenzene, chlorobenzene, bromobenzene, dichlorobenzene, and dibromobenzene. Compared with the above other types of coating additives, hexachlorobenzene has higher residual carbon content and chlorine content, and can provide more highly active gaseous carbon-chlorine free radicals and chlorine free radicals. Therefore, the coating additive is more preferably hexachlorobenzene.
[0047] Furthermore, the thermal decomposition temperature of the coating additive is less than 400° C., more preferably less than 250° C. It is understood that the temperature of the sintering treatment is usually determined according to the carbonization temperature of the carbon source. Controlling the thermal decomposition temperature of the coating additive within the above range can meet the sintering temperature requirements of most carbon source materials, making the types of carbon sources that can be used more widely.
[0048] In a specific embodiment, the chemical composition of the lithium-supplemented core is Li a M b O c , wherein M includes one or more of Fe, Ni, Mn, Cu, Zn, Co, Cr, Zr, Sb, Ti, V, Mo, Sn, 1<a≤8, 0<b≤1, 0<c<7. Exemplarily, the lithium-supplemented core may be Li 5 FeO 4 , Li 2 NiO 2 , Li 6 CoO 4 , Li 2 O 2 etc., preferably Li 5 FeO 4 .
[0049] In a specific embodiment, the carbon source includes one or more of carbon black, graphene, carbon nanotubes, fullerenes, sucrose, glucose, asphalt, polydopamine, resorcinol, formaldehyde, starch, sucrose, sodium carboxymethyl cellulose, polyvinylidene fluoride, polyvinylpyrrolidone, tannic acid, polyvinyl alcohol, polypyrrole, vitamin C, polyethylene glycol, anthracene or aniline. The above carbon sources all have high electrical conductivity, and can significantly improve the electrical conductivity of the cathode lithium supplement agent after the formation of the carbon coating layer. It is worth mentioning that when the carbon source is selected from organic carbon sources (such as sucrose, glucose, asphalt, polydopamine, resorcinol, formaldehyde, starch, sucrose, sodium carboxymethyl cellulose, polyvinylidene fluoride, polyvinylpyrrolidone, tannic acid, polyvinyl alcohol, polypyrrole, vitamin C, polyethylene glycol, anthracene or aniline, etc.), the halogen radicals generated during the thermal decomposition of the coating additive can combine with the hydrogen atoms in the organic carbon source to be removed in the form of hydrogen chloride, and promote the dehalogenation reaction of the gaseous carbon halogen radicals on the surface of the lithium supplement core, thereby in-situ generating a dense and uniform carbon coating layer.
[0050] In a specific embodiment, the mass ratio of the lithium supplement core, the carbon source and the coating additive is 1 : x : y, where 0 < x < 10% and 0 < y < 10%. Within the above mass ratio range, it is beneficial to achieve a dense and uniform coating of the carbon coating layer on the surface of the lithium supplement core, and it can also avoid the negative impact of too large a mass ratio of the conductive carbon layer on the lithium supplement capacity of the cathode lithium supplement agent.
[0051] In a preferred embodiment, the D50 particle size of the cathode lithium supplement agent is 10 - 30 μm. When the D50 of the cathode lithium supplement agent is less than 10 μm, the particles are prone to agglomeration and the contact area with the electrolyte is too large, which easily leads to gas generation due to decomposition; when the D50 of the cathode lithium supplement agent is greater than 30 μm, the specific surface area of the material is too small, which is not conducive to the exertion of the lithium supplement capacity. Exemplarily, the D50 particle size of the cathode lithium supplement agent can be 10 μm, 11 μm, 13 μm, 15 μm, 17 μm, 19 μm, 20 μm, 21 μm, 23 μm, 25 μm, 27 μm, 29 μm, 30 μm or any range composed of any two of the above values. The D50 particle size of the cathode lithium supplement agent can be regulated by jointly using the particle size of the lithium supplement core and the thickness of the coating layer.
[0052] Furthermore, the thickness of the carbon coating layer is 100~200nm. If the thickness of the carbon coating layer is too large, it will be unfavorable to improve the energy density of the battery; if the thickness of the carbon coating layer is too small, it will be difficult to fully and effectively protect the lithium-supplemented core, resulting in poor environmental tolerance. The thickness of the carbon coating layer is controlled within the above range, while achieving effective protection of the lithium-supplemented active material and reducing the adverse effect on the battery energy density. Exemplarily, the thickness of the carbon coating layer can be 100nm, 120nm, 140nm, 160nm, 180nm, 200nm or a range consisting of any two of the above values.
[0053] By controlling the above conditions, the positive electrode lithium supplement can have a lower porosity and a smaller specific surface area. Specifically, the specific surface area of the positive electrode lithium supplement is 0.3~0.8m 2 / g.
[0054] A second aspect of the present invention provides a method for preparing the positive electrode lithium supplement as described above, comprising the following steps:
[0055] The lithium supplement core, the carbon source and the coating additive are mixed to obtain a mixture; the mixture is sintered to obtain a positive electrode lithium supplement agent;
[0056] The coating additive includes a compound that can be thermally decomposed to generate gaseous carbon-halogen free radicals and halogen free radicals, wherein the thermal decomposition temperature is not higher than the sintering treatment temperature.
[0057] The above method realizes in-situ dense coating of the carbon coating layer on the surface of the lithium replenishing core by solid phase mixed sintering, and obtains a positive electrode lithium replenishing agent whose peak intensities of G peak, D peak and 1 peak satisfy 0.85 < IG / ID <1.25, 9 < IG / I1 <50, 9 < ID / I1 <50. This method does not require the addition of solvents, is more efficient and convenient, and is conducive to industrial production.
[0058] Furthermore, the temperature of the sintering treatment is 80-1000°C; the time is 3-15 hours, preferably 3-15 hours. When the carbon source is selected from inorganic materials such as carbon black, graphene, carbon nanotubes, fullerenes, etc., the sintering treatment can be carried out at a lower temperature, such as 80-300°C; when the carbon source is selected from organic materials such as sucrose, glucose, asphalt, polydopamine, resorcinol, formaldehyde, starch, sucrose, sodium carboxymethyl cellulose, polyvinylidene fluoride, polyvinyl pyrrolidone, tannic acid, polyvinyl alcohol, polypyrrole, vitamin C, polyethylene glycol, anthracene or aniline, the sintering treatment needs to be carried out at a higher temperature to ensure the carbonization of the organic matter, such as 500-1000°C.
[0059] In order to avoid interference from impurities and moisture in the air, the sintering process is carried out under an inert atmosphere, wherein the inert gas can be selected from one or more of argon, nitrogen, helium, and neon.
[0060] In a specific embodiment, the lithium-supplemented core can be obtained by mixing a lithium source and an M source in a stoichiometric ratio and then sintering the mixture. The present invention does not specifically limit the types of the lithium source, the M source, and the A source, wherein the lithium source includes but is not limited to LiOH, Li 2 O. Li 2 O 2 , Li 2 CO 3 One or more of; M source includes but is not limited to one or more of oxides, hydroxides, carbonates, and nitrates of element M.
[0061] Furthermore, the sintering temperature during the preparation of the lithium-supplemented core is 80-1000°C, preferably 700-900°C; the sintering time is 3-15 hours, preferably 7-12 hours; the heating rate is 3-10°C / minute, preferably 4-7°C / minute. The sintering process can be carried out in a muffle furnace. After the sintering is completed, in order to avoid the sudden cooling structure change of the material, the material after sintering can be naturally cooled to room temperature with the furnace cooling before being taken out.
[0062] The third aspect of the present invention provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode lithium supplement provided by the first aspect of the present invention.
[0063] Since the positive electrode plate of the present invention includes the positive electrode lithium replenishing agent, it can exert excellent lithium replenishing effect and environmental stability when used in batteries.
[0064] The positive electrode current collector of the present invention can be selected from positive electrode current collectors commonly used in the art, such as aluminum foil.
[0065] The positive electrode active material layer of the present invention includes components such as positive electrode active material, conductive agent and binder in addition to the positive electrode lithium supplement.
[0066] Among them, the positive electrode active material includes but is not limited to one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium manganese oxide, nickel cobalt manganese ternary material, nickel cobalt aluminum ternary material, lithium iron phosphate, lithium nickel manganese oxide, lithium-rich manganese-based materials, etc.
[0067] The conductive agent includes, but is not limited to, one or more of conductive carbon black, Super-C, acetylene black, Ketjen black, and carbon nanofiber.
[0068] The binder includes, but is not limited to, one or more of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC-Na), polyvinyl pyrrolidone, polytetrafluoroethylene, and styrene-butadiene rubber (SBR).
[0069] The more positive electrode lithium replenisher there is in the positive electrode active material layer, the better the lithium replenishment effect can be achieved. However, too much positive electrode lithium replenisher will inevitably lead to a decrease in the content of positive electrode active material, which is not conducive to the improvement of the positive electrode sheet capacity and battery energy density. Based on the above considerations, the mass content of the positive electrode active material in the positive electrode active material layer is controlled to be no less than 80%, and the mass content of the positive electrode lithium replenisher is less than 10%.
[0070] In a specific embodiment, the positive electrode sheet can be prepared by the following method: the positive electrode active material, the positive electrode lithium supplement, the conductive agent and the binder are dispersed in a solvent in proportion to obtain a slurry, and the slurry is then coated on at least one surface of the positive electrode collector, and the positive electrode sheet can be obtained after drying, slitting and rolling.
[0071] The fourth aspect of the present invention provides a battery, comprising the positive electrode plate provided in the third aspect. Since the battery comprises the positive electrode plate having the positive lithium supplement, the battery has a higher first cycle coulomb efficiency and a more excellent cycle performance during use.
[0072] The battery of the present invention includes, in addition to the above-mentioned positive electrode sheet, a negative electrode sheet, an electrolyte and a separator.
[0073] Among them, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer arranged on at least one surface of the negative electrode current collector. Among them, the negative electrode current collector can be selected from the negative electrode current collectors conventionally used in the art, such as copper foil. The negative electrode active material layer can also refer to the conventional composition in the art, for example, the negative electrode active material layer includes a negative electrode active substance, a conductive agent and a binder. The negative electrode active substance can be selected from the negative electrode active substances conventionally used in the art, including but not limited to one or more of natural graphite, artificial graphite, silicon-carbon material, silicon-oxygen material, and hard carbon. The composition of the conductive agent and the binder can refer to the types of conductive agents and binders in the positive electrode plate, which will not be repeated here.
[0074] The function of the separator is to separate the positive electrode plate and the negative electrode plate to prevent the two from contacting and short-circuiting, and to allow lithium ions to pass freely. The present invention does not specifically limit the type of separator, and it can be selected from porous separators with good chemical stability and mechanical stability commonly used in the art, including but not limited to one or more of polypropylene, polyethylene, glass fiber, and non-woven fabrics.
[0075] The electrolyte is a medium present between the positive electrode plate and the negative electrode plate for conducting lithium ions. It can be a gel, solid or liquid electrolyte. The present application does not specifically limit the type of electrolyte, and it can be selected from the gel, solid or liquid electrolytes commonly used in the art.
[0076] In a specific embodiment, the battery of the present invention can be prepared by the following method: stacking the positive electrode sheet, the separator and the negative electrode sheet in sequence, obtaining a battery core through a lamination or winding process, and then baking, injecting, forming, packaging and other processes to obtain the battery of the present invention.
[0077] The fifth aspect of the present invention provides an electric device, comprising the battery as described above. The present invention does not specifically limit the type of electric device, and it can be any electric device comprising the battery, including but not limited to mobile phones, portable devices, laptop computers, electric bicycles, electric cars, electric toys, energy storage devices, etc.
[0078] The following will introduce the positive electrode lithium supplement agent provided by the present invention and its preparation method and application in detail through specific examples.
[0079] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.
[0080] In the following embodiments and comparative examples, the carbon coating thickness is tested by using a CP-SEM test method, firstly cutting the sample by CP, then observing its microscopic morphology in SEM to determine the coating thickness.
[0081] D50 particle size test method: Use Malvern laser particle size analyzer to detect the particle size distribution of particles, and take the particle size value corresponding to when the cumulative distribution percentage reaches 50%.
[0082] In the following embodiments, the particle size of the positive electrode lithium supplement agent D50 is regulated by selecting lithium supplement core materials with different particle sizes and controlling the thickness of the conductive carbon layer.
[0083] Example 1
[0084] This embodiment provides a positive electrode lithium supplement agent, including a lithium supplement core and a carbon coating layer coated on the surface of the lithium supplement core, wherein the composition of the lithium supplement core is Li 5 FeO 4 The thickness of the carbon coating layer is 100 nm, the D50 particle size of the positive electrode lithium supplement agent is 20 μm, and the preparation method thereof comprises the following steps:
[0085] 1) lithium hydroxide and iron oxide are mixed and ground in a molar ratio of 5:0.5 to obtain a first mixture; the first mixture is placed in a muffle furnace, and the temperature is increased to 700°C at a heating rate of 6°C / min under a nitrogen atmosphere, and the mixture is kept at this temperature for 12 hours and then cooled to room temperature with the furnace to obtain Li 5 FeO 4 powder.
[0086] 2) Li 5 FeO 4 Powder, coating additive C 6 Cl 6 and carbon black were uniformly mixed in a mass ratio of 100:0.2:2 to obtain a second mixture; under a nitrogen atmosphere, the second mixture was heated to 200°C at a heating rate of 5°C / min, kept warm for 3 hours, and then naturally cooled to room temperature to obtain a positive electrode lithium supplement.
[0087] Example 2
[0088] This embodiment provides a positive electrode lithium supplement agent, including a lithium supplement core and a carbon coating layer coated on the surface of the lithium supplement core, wherein the composition of the lithium supplement core is Li 5 FeO 4 The thickness of the carbon coating layer is 100 nm, the D50 particle size of the positive electrode lithium supplement is 20 μm, and the preparation method is basically the same as that of Example 1, except that: in step 2), Li 5 FeO 4 Powder, coating additive C 6 Cl 6 , the carbon black mixing ratio is changed to 100:0.5:2.
[0089] Example 3
[0090] This embodiment provides a positive electrode lithium supplement agent, including a lithium supplement core and a carbon coating layer coated on the surface of the lithium supplement core, wherein the composition of the lithium supplement core is Li 5 FeO 4 The thickness of the carbon coating layer is 100 nm, the D50 particle size of the positive electrode lithium supplement is 20 μm, and the preparation method is basically the same as that of Example 1, except that: in step 2), Li 5 FeO 4 Powder, coating additive C 6 Cl 6 , the carbon black mixing ratio is changed to 100:0.8:2.
[0091] Example 4
[0092] This embodiment provides a positive electrode lithium supplement agent, including a lithium supplement core and a carbon coating layer coated on the surface of the lithium supplement core, wherein the composition of the lithium supplement core is Li 5 FeO4 The thickness of the carbon coating layer is 100 nm, the D50 particle size of the positive electrode lithium supplement is 20 μm, and the preparation method is basically the same as that of Example 1, except that: in step 2), the coating additive is replaced by C 6 Br 6 .
[0093] Example 5
[0094] This embodiment provides a positive electrode lithium supplement agent, including a lithium supplement core and a carbon coating layer coated on the surface of the lithium supplement core, wherein the composition of the lithium supplement core is Li 5 FeO 4 The thickness of the carbon coating layer is 100 nm, the D50 particle size of the positive electrode lithium supplement agent is 20 μm, and the preparation method is basically the same as that of Example 1, except that: in step 2), the insulation time is replaced with 6 hours.
[0095] Example 6
[0096] This embodiment provides a positive electrode lithium supplement agent, including a lithium supplement core and a carbon coating layer coated on the surface of the lithium supplement core, wherein the composition of the lithium supplement core is Li 5 FeO 4 The thickness of the carbon coating layer is 150 nm, the D50 particle size of the positive electrode lithium supplement is 20 μm, and the preparation method is basically the same as that of Example 1, except that: in step 2), Li 5 FeO 4 Powder, coating additive C 6 Cl 6 , the carbon black mixing ratio is changed to 100:0.2:4.
[0097] Example 7
[0098] This embodiment provides a positive electrode lithium supplement agent, including a lithium supplement core and a carbon coating layer coated on the surface of the lithium supplement core, wherein the composition of the lithium supplement core is Li 5 FeO 4 The thickness of the carbon coating layer is 180 nm, the D50 particle size of the positive electrode lithium supplement is 20 μm, and the preparation method thereof is basically the same as that of Example 1, except that: in step 2), Li 5 FeO 4 Powder, coating additive C 6 Cl 6 , the carbon black mixing ratio is changed to 100:0.2:6.
[0099] Example 8
[0100] This embodiment provides a positive electrode lithium supplement agent, including a lithium supplement core and a carbon coating layer coated on the surface of the lithium supplement core, wherein the composition of the lithium supplement core is Li 5 FeO4 The thickness of the carbon coating layer is 100 nm, the D50 particle size of the positive electrode lithium supplement agent is 20 μm, and the preparation method is basically the same as that in Example 1, except that: in step 2), the carbon black is replaced by sucrose, and the heat treatment temperature is replaced by 900°C.
[0101] Example 9
[0102] This embodiment provides a positive electrode lithium supplement agent, including a lithium supplement core and a carbon coating layer coated on the surface of the lithium supplement core, wherein the composition of the lithium supplement core is Li 5 FeO 4 The thickness of the carbon coating layer is 100 nm, the D50 particle size of the positive electrode lithium supplement agent is 20 μm, and the preparation method is basically the same as that in Example 1, except that: in step 2), the carbon black is replaced by polyethylene glycol, and the heat treatment temperature is replaced by 900°C.
[0103] Example 10
[0104] This embodiment provides a positive electrode lithium supplement agent, including a lithium supplement core and a carbon coating layer coated on the surface of the lithium supplement core, wherein the composition of the lithium supplement core is Li 5 FeO 4 The thickness of the carbon coating layer is 100 nm, and the preparation method is basically the same as that of Example 1, except that the D50 particle size of the positive electrode lithium supplement agent is 10 μm.
[0105] Embodiment 11
[0106] This embodiment provides a positive electrode lithium supplement agent, including a lithium supplement core and a carbon coating layer coated on the surface of the lithium supplement core, wherein the composition of the lithium supplement core is Li 5 FeO 4 The thickness of the carbon coating layer is 100 nm, and the preparation method is basically the same as that of Example 1, except that the D50 particle size of the positive electrode lithium supplement agent is 30 μm.
[0107] Example 12
[0108] This embodiment provides a positive electrode lithium supplement agent, including a lithium supplement core and a carbon coating layer coated on the surface of the lithium supplement core, wherein the composition of the lithium supplement core is Li 2 NiO 2 The thickness of the carbon coating layer is 100 nm, the D50 particle size of the positive electrode lithium supplement is 20 μm, and the preparation method is basically the same as that in Example 1, except that: in step 1), the first mixture is replaced by a sample obtained by mixing and grinding lithium hydroxide and nickel oxide in a molar ratio of 2:1.
[0109] Comparative Example 1
[0110] This comparative example provides a positive electrode lithium supplement agent, including a lithium supplement core and a carbon coating layer coated on the surface of the lithium supplement core, wherein the composition of the lithium supplement core is Li 5 FeO 4 The thickness of the carbon coating layer is 100 nm, the D50 particle size of the positive electrode lithium supplement is 20 μm, and the preparation method is basically the same as that of Example 1, except that: in step 2), no coating additive C is added 6 Cl 6 , and Li 5 FeO 4 The powder and the carbon black are mixed in a mass ratio of 100:2 to obtain a second mixture.
[0111] Comparative Example 2
[0112] This comparative example provides a positive electrode lithium supplement agent, including a lithium supplement core and a carbon coating layer coated on the surface of the lithium supplement core, wherein the composition of the lithium supplement core is Li 2 NiO 2 The thickness of the carbon coating layer is 100 nm, the D50 particle size of the positive electrode lithium supplement is 20 μm, and the preparation method is basically the same as that of Example 12, except that: in step 2), no coating additive C is added 6 Cl 6 , and Li 2 NiO 2 The powder and the carbon black are mixed in a mass ratio of 100:2 to obtain a second mixture.
[0113] Test Case
[0114] The following performance tests were performed on the positive electrode lithium supplement agents of the above embodiments and comparative examples:
[0115] 1. Resistivity
[0116] Test method: At 25°C, a powder resistivity meter was used to test the resistivity of the positive electrode lithium supplement. The test results are shown in Table 1.
[0117] 2. Specific surface area
[0118] Test method: Select about 1 mg of sample for testing. Use multi-point BET detection method, and the adsorption gas is N 2 , the adsorption temperature is -195°C. The test results are shown in Table 1.
[0119] 4. Moisture absorption rate
[0120] Test method: The moisture absorption rate of the positive electrode lithium supplement is tested in a constant temperature and humidity chamber at 25°C and 40% humidity, with a test interval of 20 minutes. The moisture absorption rate of the material is obtained according to the formula v=(m1-m2) / t, where m1 and m2 are the mass of the material before and after the test, respectively, and t is the test interval, which is 20 minutes here. The test results are shown in Table 1.
[0121] 5. Residual alkali content
[0122] Test method: Use methanol as solvent to dissolve the residual alkali on the surface of the positive electrode lithium supplement to obtain the test solution, perform potentiometric titration test on the test solution, use 0.01M HCl standard solution for titration to obtain the titration curve, and test the LiOH and Li 2 CO 3 The test results are shown in Table 1.
[0123] 6. Raman spectroscopy test
[0124] Test method: The test laser wavelength is 532 nm, and the collection wave number range is 100~5000 cm -1 , the Raman spectrum was obtained by testing, and the G peak, D peak and 1 peak were determined according to the displacement value of the Raman spectrum. The spectrum was analyzed to obtain its peak intensity value, and IG / ID, IG / I1 and ID / I1 were calculated. The results are listed in Table 1.
[0125] Figure 3 is the Raman spectrum of the positive electrode lithium supplement agent of Example 11, as shown Figure 3 As shown, the positive electrode lithium supplement includes a displacement range of 1560~1580cm -1 The G peak and displacement range are 1350~1370cm -1 The D peak and displacement range are 655~675cm -1 The calculated peak is IG / ID: 0.97, IG / I1: 17, and ID / I1: 17.
[0126] 7. SEM test
[0127] Test method: The positive electrode lithium supplement agents of Example 1 and Comparative Example 1 were tested by scanning electron microscopy (SEM). Figure 4 This is a SEM image of the positive electrode lithium supplement agent of Example 1. Figure 5 This is the SEM image of the positive electrode lithium supplement agent of Comparative Example 1. Figure 1 and Figure 2 It can be seen that compared with the positive electrode lithium replenisher of Comparative Example 1, the carbon coating layer on the surface of the positive electrode lithium replenisher of Example 1 is denser.
[0128] Table 1
[0129]
[0130] The following conclusions can be drawn from Table 1:
[0131] 1) By comparing Examples 1 to 12 with Comparative Examples 1 to 2, it can be seen that when the peak intensity IG of the G peak, the peak intensity ID of the D peak, and the peak intensity I1 of the 1 peak of the Raman spectrum satisfy 0.85<IG / ID<1.25, 9<IG / I1<50, and 9<ID / I1<50, the density of the coating layer is good, the resistivity of the positive electrode lithium supplement agent is significantly lower, and the specific surface area, moisture absorption rate, and residual alkali content are also at a relatively low level.
[0132] 2) By comparing Examples 1 to 3, it can be seen that with the increase in the content of the coating additive, the proportion of the G peak intensity of the positive electrode lithium supplement gradually increases, indicating that the carbon coating layer of the positive electrode lithium supplement has a higher degree of graphitization, enhanced conductivity, gradually decreased resistivity, and gradually decreased specific surface area, and the moisture absorption rate and residual alkali level of the material also decrease accordingly.
[0133] 3) By comparing Examples 1 and 4, it can be seen that compared with C 6 Br 6 , C 6 Cl 6 The coating layer formed as a coating additive has a better coating effect and a lower residual alkali content on its surface.
[0134] 4) By comparing Examples 1 and 5, it can be seen that the longer the sintering and heat preservation time of the carbon coating layer is, the more thorough the decomposition time of hexachlorobenzene is, the better the coating effect is, the greater the proportion of G peak intensity is, and the smaller the specific surface area, resistivity, moisture absorption rate and residual alkali content are.
[0135] 4) By comparing Examples 1, 6, and 7, it can be seen that as the thickness of the carbon coating layer increases, the proportion of the G peak intensity of the positive electrode lithium supplement gradually increases, indicating that the carbon coating layer of the positive electrode lithium supplement has a higher degree of graphitization, enhanced conductivity, a gradual decrease in resistivity, a gradual decrease in specific surface area, and a decrease in the moisture absorption rate and residual alkali level of the material.
[0136] 5) According to the comparison of Examples 1, 8, and 9, it can be seen that different types of carbon sources have little effect on the coating effect. Different types of organic carbon sources and inorganic carbon sources such as carbon black, sucrose, and polyethylene glycol can make the positive electrode lithium supplement have lower resistivity, lower specific surface area, lower dilution rate, and residual alkali level.
[0137] 6) According to the comparison of Examples 1, 10, and 11, it can be seen that as the particle size of the positive electrode lithium supplement D50 increases, the specific surface area becomes smaller, the contact area with the air becomes smaller, it is not easy to absorb moisture and deteriorate, and the resistivity, moisture absorption rate, and residual alkali level show a gradually decreasing trend, showing a better coating effect.
[0138] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A positive electrode lithium supplement, characterized in that: It comprises a lithium-supplementing core and a carbon coating layer coated on the surface of the lithium-supplementing core; The Raman spectrum of the positive electrode lithium supplement has a shift interval of 1560-1580cm -1 The G peak and displacement range are 1350~1370cm -1 The D peak and displacement range are 655~675cm -1 1 peak; Among them, the peak intensity IG of the G peak, the peak intensity ID of the D peak and the peak intensity I1 of the 1 peak satisfy: 0.85 < IG / ID <1.25, 9 < IG / I1 <50, 9 < ID / I1 <50.
2. The positive electrode lithium supplement according to claim 1, characterized in that: The positive electrode lithium supplement agent is obtained by sintering a mixture including a lithium supplement core, a carbon source and a coating additive; The coating additive includes a compound that can be thermally decomposed to generate gaseous carbon-halogen free radicals and halogen free radicals, and the temperature of the thermal decomposition is not higher than the temperature of the sintering treatment.
3. The positive electrode lithium supplement according to claim 2, characterized in that: The molecular weight of the coating additive is less than 600.
4. The positive electrode lithium supplement according to claim 2 or 3, characterized in that: The coating additive includes one or more of hexachlorobenzene, hexabromobenzene, chlorobenzene, bromobenzene, dichlorobenzene and dibromobenzene.
5. The positive electrode lithium supplement according to any one of claims 1 to 4, characterized in that: The chemical composition of the lithium-supplemented core is Li a M b O c , wherein M includes one or more of Fe, Ni, Mn, Cu, Zn, Co, Cr, Zr, Sb, Ti, V, Mo, and Sn, 1<a≤8, 0<b≤1, and 0<c<7.
6. The positive electrode lithium supplement according to any one of claims 1 to 5, characterized in that: The carbon source includes one or more of carbon black, graphene, carbon nanotubes, fullerene, sucrose, glucose, asphalt, polydopamine, resorcinol, formaldehyde, starch, sucrose, sodium carboxymethyl cellulose, polyvinylidene fluoride, polyvinyl pyrrolidone, tannic acid, polyvinyl alcohol, polypyrrole, vitamin C, polyethylene glycol, anthracene or aniline.
7. The positive electrode lithium supplement according to any one of claims 2 to 4, characterized in that: The mass ratio of the lithium supplement core, the carbon source and the coating additive is 1:x:y, 0 <x<10%,0<y<10%。 8. The positive electrode lithium supplement according to any one of claims 1 to 7, characterized in that: The D50 particle size of the positive electrode lithium supplement is 10-30 μm.
9. The positive electrode lithium supplement according to claim 8, characterized in that: The thickness of the carbon coating layer is 100-200 nm.
10. The positive electrode lithium supplement according to any one of claims 1 to 9, characterized in that: The specific surface area of the positive electrode lithium supplement is 0.3-0.8 m 2 / g.
11. A method for preparing a positive electrode lithium supplement according to any one of claims 1 to 10, characterized in that: The following steps are involved: The lithium supplement core, the carbon source and the coating additive are mixed to obtain a mixture; the mixture is sintered to obtain a positive electrode lithium supplement agent; The coating additive includes a compound that can be thermally decomposed to generate gaseous carbon-halogen free radicals and halogen free radicals, and the temperature of the thermal decomposition is not higher than the temperature of the sintering treatment.
12. The preparation method according to claim 11, characterized in that: The sintering process is performed at a temperature of 80 to 1000° C. and for a time of 3 to 15 hours.
13. A positive electrode plate, characterized in that: The invention comprises a positive electrode current collector and a positive electrode active material layer arranged on at least one side surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode lithium supplement agent according to any one of claims 1 to 10.
14. A battery, characterized in that: Including the positive electrode sheet as described in claim 13.
15. An electrical equipment, characterized in that: Comprising the battery of claim 14.
Citation Information
Patent Citations
Positive lithium supplement additive, positive pole piece, preparation method of positive pole piece and lithium ion battery
CN114079086A
Lithium supplement additive precursor, preparation method thereof and lithium supplement additive
CN115286043A
Lithium supplement agent suitable for high-voltage positive electrode as well as preparation method and application of lithium supplement agent
CN115863797A
Composite lithium supplementing material and preparation method and application thereof
CN117012929A
Lithium supplement agent and preparation method thereof, positive pole piece and secondary battery
CN117219777A
Cited By
Lithium supplement agent and preparation method thereof, positive pole piece, battery and electric equipment
CN121307031A
Positive plate, preparation method thereof and battery
CN122025547A
Positive electrode lithium-supplementing agent, preparation method therefor, positive electrode sheet, battery, and electrical device
WO2026092715A1